5G: A new future for Mobile Network Operators, or not?. (April 2021) - Lehr, William; Queder, Fabian; Haucap, Justus
Abstract: The transition to 5G has the potential to significantly disrupt the competitive landscape for wireless services. For Mobile Network Operators (MNOs), 5G represents the next generation of cellular technology. However, the order-of-magnitude performance improvements targeted by 5G, its design philosophy that embraced a wider range of contributors than participated in the development of earlier generations of cellular technology, and by its focus on expanding the range of markets to be addressed by cellular technologies, 5G represents a paradigm shift. It is more of a tool-box of capabilities than a one-size-fits-all technology. This paper compares and contrasts 5G with earlier generations of cellular and related wireless technologies and examines how the economic forces that have shaped the MNO industry heretofore are changed with 5G. This examination highlights the potential for new business models and competition to disrupt the wireless industry in coming years. Highlights: 5G, next generation of mobile cellular technology represents a paradigm shift relative to earlier generations. 5G has the potential to disrupt mobile broadband competition. 5G compared to earlier generations of cellular technologies and impact on economic forces that shaped industry analyzed. Analyzes transition to small cell architectures, intelligent core network, and shared spectrum needed for 5G. Competitive dynamics explored for how MNOs will address core market as well as new opportunities enabled by 5G.